1982
DOI: 10.1111/j.1399-6576.1982.tb01886.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Receptor Blocker Withdrawal. A Preoperative Problem in General Surgery?

Abstract: A prospective randomized study was performed in 91 patients scheduled for general surgery on 99 occasions. The patients were chronically ( > 3 months) treated with P-receptor blockers because of ischaemic heart disease and/or hypertension and the P-receptor blockade was either gradually withdrawn (n=51) during 4 days preoperatively or continued until surgery (n=48). The effects on arterial blood pressure (BP), heart rate (HR) and rate-pressure product (RPP) at rest and the incidence ofchest pain duringdaily ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…12 The evidence for this recommendation was mainly on the basis of the body of literature pertaining to the dangers of beta blocker withdrawal that has been accumulating for more than 3 decades. 13,14 Not only is perioperative withdrawal of beta blockade associated with myocardial ischemia, but a recent prospective cohort study also showed that the risk of myocardial infarction (MI) increased substantially by withdrawal of cardioselective beta blockade. 15 The reasons for developing beta blocker withdrawal complications, which typically begins 72 hours after cessation of the drugs, include heightened sensitization to endogenous catecholamines, resulting in an increase in sympathetic nervous system activity.…”
Section: Beta Blockersmentioning
confidence: 98%
“…12 The evidence for this recommendation was mainly on the basis of the body of literature pertaining to the dangers of beta blocker withdrawal that has been accumulating for more than 3 decades. 13,14 Not only is perioperative withdrawal of beta blockade associated with myocardial ischemia, but a recent prospective cohort study also showed that the risk of myocardial infarction (MI) increased substantially by withdrawal of cardioselective beta blockade. 15 The reasons for developing beta blocker withdrawal complications, which typically begins 72 hours after cessation of the drugs, include heightened sensitization to endogenous catecholamines, resulting in an increase in sympathetic nervous system activity.…”
Section: Beta Blockersmentioning
confidence: 98%
“…It might contribute to adverse myocardial outcome because of a rebound effect, resulting in increased HR, blood pressure and plasma noradrenalin concentrations [55][56][57][58][59]. Redelmeier et al demonstrated that longer acting b-blockers (such as atenolol) have a better perioperative cardiac protective action than short-acting drugs (metoprolol), probably as a result of acute withdrawal effects from missed doses of short-acting b-blockers [60].…”
Section: Withdrawalmentioning
confidence: 99%
“…Therefore, b-blockers should be continued in patients already using them [16,[57][58][59][60][61][62][63][64] COPD: Chronic obstructive pulmonary disease; FEV-1: Forced expiratory volume in one second.…”
Section: Side Effect Take Home Messagementioning
confidence: 99%
“…28,28a There is some concern among anesthesiologists that continuing ␤-blocker therapy into the perioperative period could attenuate or mask the physiologic responses to anemia, hypoxia, and hypercarbia. 29 However, abrupt withdrawal of these medications may sensitize patients to endogenous catecholamines, resulting in hypertension, tachycardia, arrhythmias, and myocardial ischemia. 30 -31a In one study, Ponten et al 29 examined the effects of slow withdrawal of ␤-blockers in 91 patients chronically treated with a ␤-blocker and scheduled to undergo general anesthesia.…”
Section: ␤-Adrenergic Blockersmentioning
confidence: 99%
“…29 However, abrupt withdrawal of these medications may sensitize patients to endogenous catecholamines, resulting in hypertension, tachycardia, arrhythmias, and myocardial ischemia. 30 -31a In one study, Ponten et al 29 examined the effects of slow withdrawal of ␤-blockers in 91 patients chronically treated with a ␤-blocker and scheduled to undergo general anesthesia. The control group continued taking the ␤-blocker up to the morning of surgery, while the experimental group was withdrawn from ␤-blocker therapy withdrawn during a 4-day period before the surgery.…”
Section: ␤-Adrenergic Blockersmentioning
confidence: 99%